The Relationship Between Character Education and Indonesian Language Learning Outcomes - Zalukhu, Mardian; Bulolo, Yanida; Gulo, Fiman Astrid Nan Dinda; Zendrato, Harapan (Journal of Computer Science Advancements, 2024)
Character education plays a crucial role in shaping students' Indonesian learning skills. This study adopts a qualitative approach with a descriptive method to explore the relationship between character education and Indonesian learning outcomes among grade X students in secondary school. Data collection tools include classroom observation Character education plays a crucial role in shaping students' Indonesian learning skills. This study adopts a qualitative approach with a descriptive method to explore the relationship between character education and Indonesian learning outcomes among grade X students in secondary school. Data collection tools include classroom observation Character education plays a crucial role in shaping students' Indonesian learning skills. This study adopts a qualitative approach with a descriptive method to explore the relationship between character education and Indonesian learning outcomes among grade X students in secondary school. Data collection tools include classroom observation